Immunohistochemistry of small blue round cell tumors - Gown, A. M.; Bacchi, C. E. (Natl Soc Histotechnology, 2002)
Small blue round cell tumors (SBRCTs) are a set of malignancies that have a particular proclivity for the pediatric age group. These tumors are notoriously difficult to distinguish by histologic evaluation alone, and in recent years a number of new immunohistochemical markers have emerged that can aid in the correct categorization of these lesions. Myogenin, a muscle-restricted nuclear transcription factor, has been demonstrated to be a highly sensitive and specific marker of rhabdomyosarcoma, and is superior to previous markers such as myoglobin, muscle actins, and desmin. The FlI-1 gene product is expressed as part of the EWS/FLI-1 novel chimeric protein that results from the t(11;22)(q24;q12) translocation that occurs in approximately two-thirds of cases of PNET/Ewings sarcoma. Immunohistochemical detection of the FLI-1 gene product can thus complement detection of CD99/MIC2 for the positive identification of PNET/Ewings sarcoma. Markers of neuroblastoma include neural markers, such as chromogranin A, neurofilaments, and synaptophysin. Desmoplastic small round cell tumor (DSRCT) is a tumor with an unusual immunophenotype, including co-expression of cytokeratin, vimentin, and desmin; recent studies have also documented the use of antibodies to the WT-1 gene product as a marker of the chimeric EWS/WT-1 protein formed as a result of the t(11;22)(p13;q12) translocation that characterizes this unique tumor. In summary, there now exists a panel of antibodies defining immunohistochemical markers of individual SBRCTs that can identify rhabdomyosarcoma, PNET/Ewings sarcoma, neuroblastoma, and DSRCT with high sensitivity and specificity.